Uncovering karst endemism within Borneo: two new Cyrtodactylus species from Sarawak, Malaysia - Davis, Hayden R.; Bauer, Aaron M.; Jackman, Todd R.; Nashriq, Izneil; Das, Indraneil (Zootaxa, 2019)
The island of Borneo lies within one of the most biodiverse regions in the world. Despite this, its documented gekkonid diversity is not commensurate with other areas of Southeast Asia. The megadiverse genus Cyrtodactylus is especially underrepresented. Limestone-karst ecosystems, in particular, harbor many endemic Cyrtodactylus species, but only one karst-dwelling species is currently recognized from Borneo. This paper adds two additional karst-dwelling Cyrtodactylus species—C. muluensis sp. nov. and C. limajalur sp. nov.—from Sarawak, Malaysia. Cyrtodactylus muluensis sp. nov. is endemic to Gunung Mulu and is distinguished from its congeners by having a precloacal groove, 31–38 ventral scales, a maximum SVL of at least 88 mm, enlarged subcaudals, 19–20 subdigital lamellae, and a banded dorsal body pattern. Cyrtodactylus limajalur sp. nov. is endemic to the Serian region and is distinguished from its congeners by having 33–42 ventral scales, enlarged subcaudals, a precloacal pit, a maximum SVL of at least 94 mm, 5–6 enlarged femoral scales, 19–22 subdigital lamellae, and five distinct bands on the dorsum. Both species are phylogenetically distinct and deeply divergent from all other congeners. The description of two new karst-dwelling species highlights the need to conserve karst habitats and the endemic species they harbor.